An archaeological overview of the landscape of the al-Duqm development area, Sultanate of Oman (poster) - Genchi, Francesco; Martino, Gabriele; Maiorano, Maria Pia; Garba, Roman; Al-Ghafri, Waleed Hamad (Proceedings of the Seminar for Arabian Studies, 2017)
The aAl-Duqm area (al-WusΓā administrative division, Sultanate of Oman) is located in eastern-central Oman and is marked by a relatively flat topography (Quaternary Period sedimentary cover) with some residual hills (mostly Upper Cretaceous to Lower Tertiary). In November–December 2015 the whole area, which is covered by the Special Economic Zone Authority of Duqm (SEZAD), was surveyed with the main aim of assessing the archaeological potential and related risks of this area, now affected by rapid development. The team recorded about 900 archaeological finds, ranging from a single hearth to clusters of tumuli tombs, flint scatters, triliths clusters, and stratified open-air sites. It encountered archaeological remains from a wide chronological period, ranging from at least the Late Pleistocene, with some earlier less certain evidence, to the early first millennium AD. The huge amount of data, all conveyed in a GIS (geographic information system) database, will be used for academic purposes (research in land-use modalities, resource acquisition strategies, population dynamics) and as an analytical tool of the Ministry of Heritage and Culture (MOHC). The collected data will be used in all phases of the archaeological valorization and preservation of the archaeological heritage within the SEZAD area.